The fight against unemployment in Algeria: Entrepreneurship as a key lever for the professional integration of young graduates - DJELLAB, Mohamed; KHELIFA, Abdenour (Art Law and Accounting Reporter, 2025)
The professional integration of young graduates has, for more than a decade, been one of the major policy challenges for the Algerian state. This is particularly true in a societal context characterized by a predominantly young population—most of whom are under the age of 30—and a persistently high unemployment rate among university graduates (17.7% in September 2016, according to the National Statistics Office). In response, various public ministries have undertaken efforts to combat unemployment and facilitate the integration of young people into the labor market. As a result, several programs such as ANSEJ, ANGEM, CNAC and ANEM have emerged. Along the same lines, Algerian universities have also contributed through different mechanisms they have implemented, including the ME, the BLEU, the CDC and the CRE. This article examines the role of the university in promoting the professional integration of its graduates. It also analyzes a specific project that involved several Algerian and international institutions, including the Ministry of Higher Education and the International Labour Organization: the “Tawdif Project: From University to the World of Work.” Particular attention is given to the CLE program, “Understanding the Enterprise,” which emphasizes the promotion of entrepreneurial culture across all disciplines and fields within Algerian universities.
Keywords: Unemployment; Youth; University; Graduates; Employment; Entrepreneurship